Evidence-Based Effects of High-Intensity Interval Training on Exercise Capacity and Health: A Review with Historical Perspective - Atakan, Muhammed Mustafa (Int J Environ Res Public Health, 2021)
Engaging in regular exercise results in a range of physiological adaptations offering benefits for exercise capacity and health, independent of age, gender or the presence of chronic diseases. Accumulating evidence shows that lack of time is a major impediment to exercise, causing physical inactivity worldwide. This issue has resulted in momentum for interval training models known to elicit higher enjoyment and induce adaptations similar to or greater than moderate-intensity continuous training, despite a lower total exercise volume. Although there is no universal definition, high-intensity interval exercise is characterized by repeated short bursts of intense activity, performed with a “near maximal” or “all-out” effort corresponding to ≥90% of maximal oxygen uptake or >75% of maximal power, with periods of rest or low-intensity exercise. Research has indicated that high-intensity interval training induces numerous physiological adaptations that improve exercise capacity (maximal oxygen uptake, aerobic endurance, anaerobic capacity etc.) and metabolic health in both clinical and healthy (athletes, active and inactive individuals without any apparent disease or disorder) populations. In this paper, a brief history of high-intensity interval training is presented, based on the novel findings of some selected studies on exercise capacity and health, starting from the early 1920s to date. Further, an overview of the mechanisms underlying the physiological adaptations in response to high-intensity interval training is provided.